The Influence Of Service Quality, Promotions, And Electronic Word Of Mouth (E-Wom) On Purchasing Decisions In The Tokopedia Marketplace - Melia,; Rauly Sijabat,; ,Ratih Hesty Utami, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of service quality, promotions and electronic word of mouth on purchasing decisions both partially and simultaneously on the Tokopedia marketplace. This research uses quantitative research methods, with a generation Z population of online shop users. The number of samples used was 384 respondents. The data collection process was carried out through distributing questionnaires. Data analysis used SPSS 23. The method used was multiple linear regression analysis. The research results show that there is a positive and significant influence between the service quality variable (X1) on the variable (Y) in the Tokopedia marketplace. There is a positive and significant influence between the promotion variable (X2) on the variable (Y). There is a positive and significant influence between the electronic word of mouth variable (X3) on the variable (Y). The results of simultaneous testing show that there is an influence on the variables of service quality, promotion, and electronic word of mouth on purchasing decisions on the Tokopedia marketplace for generation Z online shop users.